Aspects of VLA-4 and LFA-1 regulation that may contribute to rolling and firm adhesion - Chigaev, Alexandre; Sklar, Larry A. (Frontiers in Immunology, 2012)
Very Late Antigen -4 (CD49d/CD29, alpha4 beta1) and Lymphocyte Function-associated Antigen-1 (CD11a/CD18, alphaL beta2) integrins are representatives of a large family of adhesion receptors widely expressed on immune cells. They participate in cell recruitment to sites of inflammation, as well as multiple immune cell interactions. A unique feature of integrins is that integrin-dependent cell adhesion can be rapidly and reversibly modulated in response to cell signaling, because of a series of conformational changes within the molecule, which include changes in the affinity of the ligand binding pocket, molecular extension (unbending) and others. Here, we provide a concise comparative analysis of the conformational regulation of the two integrins with specific attention to the physiological differences between these molecules. We focus on recent data obtained using a novel technology, based on small fluorescent ligand-mimicking probes for the detection of integrin conformation in real-time on live cells at natural receptor abundance.